Observation of the body mass index of patients immunosuppressed by HIV / AIDS as aid in nutritional fitness - da Cruz Araújo, Claudielly; de Souza Rodrigues, Cristina; de Moura Lira, Thayna; Müller, Deisi Laís; de Sousa Silva, Raynara Karen; Souza de Carvalho, Patrícia Cristina; Menezes de Azevedo, Weverson; Araújo Freire, Daniel; Portela de Azevedo, Arimatéia (Revista Feridas, 2021)
Introduction: In the set of changes caused by the nutritional condition of the hospitalized patient, it has an influence on his clinical evolution and the ability to identify it on admission, making it effective to ensure adequate support from the multidisciplinary team, since the role played by nutrition to support the health and quality of life of these patients is essential. Objectives: To show that the simple observation of the Body Mass Index (BMI) of hospitalized patients can contribute as an aid in nursing interventions to suggest nutritional adequacy. Methodology: Sectional, prospective, descriptive and quantitative study. Results: The profile of these showed that they were aged between 21 and 49 years old, 75% had immunosuppressive diseases (HIV / AIDS and etc.), the BMI showed that 45% had values below 18, thus characterizing a low weight and needing nutritional intervention. Of those with low weight, only 25% had weight gain during hospitalization. Conclusion: The deficit in weight gain among the investigated patients may be due to the lack of observation of some measure of nursing interventions to suggest nutritional adequacy.